STUDENTS’ DIFFICULTIES IN FINISHING A THESIS OF ENGLISH STUDY PROGRAM AT MUHAMMADIYAH UNIVERSITY OF TANGERANG - Abdul Rohim (Universitas Muhammadiyah Tangerang, 2023)
This study aims to determine the difficulties faced by students of Muhammadiyah University of Tangerang English Education Study Program in conducting research and writing a thesis as their final project in the University. This type of research is descriptive research. The subjects of this study were undergraduate students of the English education study program who were undergraduate thesis guidance in 2020. Data collection in this study used questionnaires . The questionnaire is given to students who are writing their thesis. Data were analyzed using percentage techniques which were further described. The results of the study generally show that there are various factors of difficulties faced by students in conducting research and writing it into thesis, both psychological factors and sociocultural factors. Psychological factors are caused by challenges of adapting research topics to the current situation, lack of understanding of research methods and academic writing styles and lack of motivation.. In sociocultural factors, student difficulties are dominated by social factors from their friends, parents and supervisors.